Evaluating the influence of diethyl ether on performance and emission outputs in KIRLOSKAR TV-I engines fueled with pumpkin seed oil biodiesel (2025)
This investigation examines the performance and emission characteristics of the KIRLOSKAR TV-I engine utilizing pumpkin seed oil (Cucurbita pepo L) methyl ester blended with 5% diethyl ether (DEE). Various blends containing 10%, 20%, 30%, 40%, and 50% pumpkin seed oil biodiesel were analysed for their chemical and physical properties, including viscosity, density, flash point, cetane number, and oxidation stability, in compliance with ASTM standards. Gas Chromatography-Mass Spectrometry (GC-MS) was employed to determine the fatty acid composition of the biodiesel. Experimental results revealed that the 20% biodiesel blend exhibited superior performance, combustion, and emission characteristics, making it a viable substitute for conventional diesel with minimal engine modifications. Emission analysis of the 20% blend showed a 0.65% reduction in carbon monoxide (CO), a 10.3% decrease in carbon dioxide (CO2), and a 21.1% reduction in nitrogen oxide (NOx) compared to diesel. Notably, blends without additives also demonstrated significant reductions in NOx (25.83%), CO (14.3%), and CO2 (13.8%) emissions, highlighting the environmental benefits of these biodiesel formulations.